2009
DOI: 10.1007/s00018-009-9149-8
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase CK2 in Health and Disease

Abstract: Within the last decade, 40 crystal structures corresponding to protein kinase CK2 (former name 'casein kinase 2'), to its catalytic subunit CK2alpha and to its regulatory subunit CK2beta were published. Together they provide a valuable, yet by far not complete basis to rationalize the biochemical features of the enzyme, such as its constitutive activity, acidophilic substrate specificity, dual-cosubstrate specificity and its heterotetrameric quarternary structure. Comprehensive sets of structural superimpositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 87 publications
(156 reference statements)
0
44
0
Order By: Relevance
“…These associate into a tetrameric holoenzyme carrying two catalytic subunits, believed to intermix so that the active tetramer can contain aa, aα′, or α′α′ forms ( 22 ). Via western blot analysis we found that MDA-MB 231 cells express both types of catalytic subunits quiescent and spreading cells.…”
Section: Resultsmentioning
confidence: 99%
“…These associate into a tetrameric holoenzyme carrying two catalytic subunits, believed to intermix so that the active tetramer can contain aa, aα′, or α′α′ forms ( 22 ). Via western blot analysis we found that MDA-MB 231 cells express both types of catalytic subunits quiescent and spreading cells.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, these three mutations are located in or close to structural elements that are crucial for CK2 activity, namely the substrate binding site, the RD and DWG motifs [41, 42]. By interfering with these regulatory elements, compound 1 and 4 may stabilize a non-productive catalytic form of CK2α.…”
Section: Discussionmentioning
confidence: 99%
“…Both optically active alcohol and ester were separated by column chromatography (99:1, dichloromethane/methanol). (R)-1-(4,5,6,7-Tetrabromo-2H-benzotriazol-2-yl)but-3-yl acetate (10) ee > 99%. Mp 135-136 • C. R f = 0.27 (dichloromethane).…”
Section: General Procedures Of Lipase-catalyzed Transesterificationmentioning
confidence: 98%
“…1 2.4.6. General procedure for preparation of racemic acetates (9)(10)(11) To a solution of racemic alcohol (0.2 mmol), DCC (45.4 mg, 0.22 mmol) and catalytic amount of DMAP in dichloromethane (10 mL), glacial acetic acid (12.6 mg, 0.22 mmol) was added and the mixture was stirred overnight at r.t. Then the mixture was filtered and the solvent was evaporated. The residue was purified by column chromatography (99:1, dichloromethane/methanol) giving pure product as white crystals.…”
Section: -(4567-tetrabromo-2h-benzotriazol-2-yl)butan-2-ol (5)mentioning
confidence: 99%
See 1 more Smart Citation